Evaluation of the clinical effectiveness of bioactive glass (S53P4) in the treatment of non-unions of the tibia and femur: study protocol of a randomized controlled non-inferiority trial - Tanner, Michael Christopher; Heller, Raban; Westhauser, Fabian; Miska, Matthias; Ferbert, Thomas; Fischer, Christian; Gantz, Simone; Schmidmaier, Gerhard; Haubruck, Patrick (Trials, 2018)
Treatment of non-union remains challenging and often necessitates augmentation of the resulting defect with an autologous bone graft (ABG). ABG is limited in quantity and its harvesting incurs an additional surgical intervention leaving the risk for associated complications and morbidities. Therefore, artificial bone graft substitutes that might replace autologous bone are needed. S53P4-type bioactive glass (BaG) is a promising material which might be used as bone graft substitute due to its osteostimulative, conductive and antimicrobial properties. In this study, we plan to examine the clinical effectiveness of BaG as a bone graft substitute in Masquelet therapy in comparison with present standard Masquelet therapy using an ABG with tricalciumphosphate to fill the bone defect.
Gesehen am 15.06.2018